2007
DOI: 10.1002/bit.21564
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for delivering exogenous material into developing zebrafish embryos

Abstract: Non-invasive manipulation of multicellular systems is important for medical and biological research. The ability to introduce, remove, or modify molecules in the intracellular environment is pivotal to our understanding of cellular structure and function. Herein, we report on an alternative method for introducing foreign material into developing embryos using the application of femtosecond (fs) laser pulses. When intense fs laser pulses are focused to a sub-micron spot, transient pores are formed, providing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 41 publications
2
69
0
Order By: Relevance
“…A recent alternative approach to microinjection has made use of lasers to photoporate material into individual cells of the small marine polychaete P. lamarckii (Torres-Mapa et al, 2011). This approach has the potential to enable fine-scale manipulations of the early embryogenesis of annelids, as well as other taxa (Kohli et al, 2007;Kohli and Elezzabi, 2008).…”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…A recent alternative approach to microinjection has made use of lasers to photoporate material into individual cells of the small marine polychaete P. lamarckii (Torres-Mapa et al, 2011). This approach has the potential to enable fine-scale manipulations of the early embryogenesis of annelids, as well as other taxa (Kohli et al, 2007;Kohli and Elezzabi, 2008).…”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…Proof of principle experiments for ablation in zebrafish were published in 2003 and 2007 [79,134]. A couple of papers specify the optimal laser parameters for femtosecond laser optoporation of embryonic cell membranes and the resulting short and long-term viabilities, which are generally above 90% [135,136]. In another study, two-photon calcium imaging identified specific spinal projection neurons whose activity correlate with stimuli evoking turns.…”
Section: Zebrafishmentioning
confidence: 99%
“…Usually a Titanium-Sapphire laser at a wavelength of approximately 800 nm and pulse duration of $100 fs is tightly focused on the cellular membrane creating a sub-micron pore that lasts a fraction of a second. The unmatched precision of the treatment has enabled a number of challenging biological experiments such as the transfection of embryonic zebrafish [7] and stem cells [8]. It was also shown that a transcription factor Elk1 mRNA optoinjected into the soma of primary neurons causes a different cellular response to mRNA injected into the dendrites [9].…”
Section: Biophotonicsmentioning
confidence: 99%